Data from: Integrating demographic niches and black spruce range expansion at subarctic treelines - Goodwin, Katie; Brown, Carissa (Borealis, 2022)
AbstractWhen investigating relationships between species’ niches and distributions, niches can be divided demographically, resulting in unique niches for different life stages. This approach can identify changing substrate requirements throughout a species’ life cycle. Using non-metric multidimensional scaling, we quantified microsite conditions associated with successful recruitment in the tundra landscape and successful seed production amongst adult trees of black spruce (Picea mariana) at subarctic treeline in Yukon, Canada to assess how life stage-specific requirements may impact the distribution of this widespread boreal tree species. Treeline ecotones in this region showed high heterogeneity in tundra microsites available for establishment. Black spruce exhibited changing microsite associations from germination to reproductive maturity, which were mainly driven by changes in plant community and soil moisture. These associations limit the microsites where individuals can establish and reproduce to a subset available within the heterogeneous landscape. Overall, we suggest that (1) substrates suitable for early recruitment are limited at the range edge; and (2) reproductive adults have a narrow niche, limiting successful seed production in adults and forming sink populations where suitable conditions are limited. Our multivariate assessment of microsite suitability can provide valuable insights into the spatial distribution of a species throughout its life cycle and identify life stage-specific constraints to range expansion.